Benchmarking vector arthropod culture: an example using the African malaria mosquito, Anopheles gambiae (Diptera: Culicidae). (December 2016) - Valerio, Laura; Matilda Collins, C.; Lees, Rosemary; Benedict, Mark
Abstract Background Numerous important characteristics of adult arthropods are related to their size; this is influenced by conditions experienced as immatures. Arthropods cultured in the laboratory for research, or mass-reared for novel control methods, must therefore be of a standard size range and known quality so that results are reproducible. Methods A simple two-step technique to assess laboratory culture methods was demonstrated using the mosquitoAnopheles gambiae s.s. as a model. First, the ranges of key development outcomes were determined using various diet levels. The observed outcomes described the physiologically constrained limits. Secondly, the same outcomes were measured when using a standard operating procedure (SOP) for comparison with the determined ranges. Results The standard method resulted in similar development rates to those of high and medium diets, wing length between those resulting from the high and medium diets, and larval survival exceeding all benchmark diet level values. The SOP used to produce experimental material was shown to produces high-quality material, relative to the biologically constrained limits. Conclusions The comparison between all possible phenotypic outcomes, as determined by biological constraints, with those outcomes obtained using a given rearing protocol is termed "benchmarking". A method is here demonstrated which could be easily adapted to other arthropods, to objectively assess important characters obtained, and methods used, during routine culture that may affect outcomes of research.